2022
DOI: 10.3389/fimmu.2022.852215
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IgLON5 Disease – The Current State of Knowledge and Further Perspectives

Abstract: Anti-IgLON5 disease is a relatively new neurological entity with the first cases reported in 2014. So far, less than 70 articles on this topic have been published. Due to its unspecific symptomatology, diverse progression, novelty and ambiguous character, it remains a difficulty for both clinical practitioners and scientists. The aim of this review is to summarize the current knowledge concerning anti-IgLON5 disease; mechanisms underlying its cause, symptomatology, clinical progression, differential diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…In total, we identified 130 novel synaptic proteins that correlate significantly with vGat and were not previously recognized as synaptic by SynGO. In the vGat core protein module we identified, for example, IgLON5, a cell adhesion protein implicated in a specific anti-IgLON5 neurodegenerative autoimmune disease (Madetko et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In total, we identified 130 novel synaptic proteins that correlate significantly with vGat and were not previously recognized as synaptic by SynGO. In the vGat core protein module we identified, for example, IgLON5, a cell adhesion protein implicated in a specific anti-IgLON5 neurodegenerative autoimmune disease (Madetko et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…NCAN is a component of neuronal extracellular matrix and is linked to neurite growth 39 . IGLON5 has been implicated in maintenance of blood–brain–barrier integrity and an anti-IGLON5 antibody disease involves the deterioration of cognitive health 40 . Taken together, the protein markers identified in the PheWAS may, therefore, reflect pathways that could be targeted to improve brain health.…”
Section: Discussionmentioning
confidence: 99%
“…Varying effectiveness of therapy is described in the literature, review of 13 patients, discovered only one showed transient improvement of symptoms [ 9 ]. Another, in a case series of 46 patients; 20 responded to immunotherapy; 15 had lasting response to treatment at follow-up [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy appears to give best response rates though no consensus exists [ 7 , 10 ]. Initial studies reported that many patients showed no improvement in symptoms with therapy, though recent suggestion is, treatment specifically within the active phase of disease, may increase efficacy of treatment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%